Treatment barriers and clinical outcome of children with medulloblastoma in China: a report from the Chinese Children's Cancer Group (CCCG). Issue 1 (17th September 2021) - Liu, Anthony Pak-Yin; Zhen, Zijun; Yang, Qunying; Yuan, Xiaojun; Ma, Xiaoli; Chen, Jianliang; Wang, Jingsheng; Yang, Lihua; Guo, Haixia; Jiang, Lian; Weng, Wenjun; Huang, Libin; et al.
Abstract: Background: Medulloblastoma (MB) is the most common malignant central nervous system tumor of childhood. Management requires interdisciplinary care and is associated with unique challenges in developing regions. Here, we report the characteristics, clinical outcome and treatment barriers for Chinese children with MB based on a multi-institutional cohort from the Chinese Children's Cancer Group (CCCG). Methods: Retrospective cohort study among 12 Chinese pediatric oncology units from the CCCG Brain Tumor Workgroup on patients aged <18 years diagnosed with MB from 2016 to 2019. Results: 221 patients (male:female = 138:83) were included, 175 (79%) were ≥3 years of age, and 46 (21%) <3 years. 177 patients (80%) were completely staged, among which 50 (28%) had metastasis and 70 (40%) were considered to have high-risk (HR) disease. Gross/near-total resection was achieved in 203 patients (92%). In patients where molecular grouping could be assigned, 19 (16%), 35 (29%), and 65 (54%), respectively had WNT-activated, SHH-activated, and Group 3/4 MB. The median duration between resection and initiation of adjuvant therapy was 36 days. Respective 2-year PFS and OS rates were 76.0 ± 3.0% and 88.0 ± 2.3%. PFS was significantly associated with age, metastatic status and clinical risk grouping. Chemotherapy use during CSI or alkylator choice were not significant predictors for patient outcome. Conclusions: We reported the clinical profiles and outcome from the largest cohort of Chinese children with MB after multi-modal therapy. Strengths and limitations on the local provision of neuro-oncology service are identified.